Developing and Compiling a Mindfulness-Based Stress Reduction Program and Evaluating its Effectiveness on Relieving Chronic Pain in the Elderly: A Case Series - Soukhtanlou, Mohammad; Pourhosein, Reza; Afrooz, Gholamali (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: This study was conducted to develop and compile a mindfulness-based stress reduction (MBSR) program within a context of physiotherapy rehabilitation to manage chronic pain in the elderlies in an Iranian clinical setting. Methods and Materials: The 8-session MBSR treatment protocol was translated, revised for the Iranian elderly, and compiled as a one-on-one therapy using a unique protocol with 20-session physiotherapy. Two volunteers aged 65 (male) and 71 (female) with knee and ankle chronic pain were selected and received the program for 8 consecutive weeks with a 3-month follow-up. Treatment satisfaction levels, adherence to treatment sessions, and patient-reported clinical outcome measures were used at baseline, immediately post-intervention, and three months following the intervention, measuring pain, anxiety, fatigue, sleep disturbance, pain interference levels, and kinesiophobia. Findings: Participants rated high satisfaction with the treatment and protocol, attending all treatment sessions and assessments. The Patient-Reported Outcomes Measurement Information System results indicated that there was a decrease in anxiety, fatigue, sleep disturbance, and pain interference for both participants. Conclusion: A brief, one-on-one MBSR program, adapted for the elderly with chronic pain, can be integrated with physiotherapy intervention in an Iranian clinical setting. The program has the potential to alleviate pain severity, kinesiophobia, anxiety, fatigue, sleep disturbances, and pain interference. High treatment satisfaction levels indicate the feasibility of evaluating the program in a future randomized controlled clinical trial to assess its effect on clinical outcomes.